Peningkatan Kemampuan Literasi Numerik Peserta Didik Kelas X Menggunakan Model Pembelajaran Problem Based Learning (PBL) Berbantu E LKPD - Nisak, Rodhotun; Rahmawati, Noviana Dini; Setiawan, Agus; Sugiyanti, Sugiyanti (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this research is to improve the mathematical numeracy literacy skills of class X.11 students at SMA N 2 Semarang using the Problem Based Learning (PBL) learning model assisted by E LKPD. This type of research is classroom action research with research subjects of 36 students in class X.11 SMA N 2 Semarang. Data collection techniques in this research used observation, tests and documentation. Data collection was carried out through a pre-test of mathematical numeracy literacy skills and a post-test of mathematical numeracy literacy skills. At the pre-cycle stage, the average value of the numerikal literacy test results was 52.56 with a completion percentage of 22.28%. In cycle 1 the average score was 66.28 with a completion percentage of 52.78%. In cycle 2 the average score was 83.98 with a completion percentage of 80.56%. See